Pengimplementasian Literasi Budayaan Di Sekolah Dasar Melalui Program Inilah Budayaku - Hikmatul Ghina; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
Cultural literacy is the ability to understand and behave towards Indonesian culture as a national identity. Implementing it certainly requires proper planning and programs. In one of the elementary schools in the Cianjur area, a program was created which could be one way of implementing cultural literacy, especially at the elementary school level. This article uses a descriptive research method that uses a qualitative approach and the techniques used are literature studies and observations (interviews).